2016
DOI: 10.1371/journal.pone.0165652
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in Type 2 Diabetes: Impact on Quality of Life and Predictors

Abstract: Fatigue is a persistent symptom, impacting quality of life (QoL) and functional status in people with type 2 diabetes, yet the symptom of fatigue has not been fully explored. The purpose of this study was to explore the relationship between fatigue, QoL functional status and to investigate the predictors of fatigue. These possible predictors included body mass index (BMI), Hemoglobin A1C (HbA1C), sleep quality, pain, number of complications from diabetes, years since diagnosis and depression. Forty-eight indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 72 publications
(58 reference statements)
7
73
1
4
Order By: Relevance
“…Indeed, fatigue is known to be prevalent in persons with type 1 and type 2 diabetes. [23][24][25] Fatigue was most pronounced in patients with lower well-being status. Persons with low mood score around 33 points (on a 0-100 scale) higher compared with persons with normal well-being, while those likely depressed score approximately 46 points as higher relative to normal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, fatigue is known to be prevalent in persons with type 1 and type 2 diabetes. [23][24][25] Fatigue was most pronounced in patients with lower well-being status. Persons with low mood score around 33 points (on a 0-100 scale) higher compared with persons with normal well-being, while those likely depressed score approximately 46 points as higher relative to normal well-being.…”
Section: Discussionmentioning
confidence: 99%
“…However, a cross-sectional study of people with T2DM showed that depression symptoms were not a predictor of fatigue severity in this population. Rather, sleep quality was found to be the strongest explanatory factor for fatigue [32]. One possible explanation for this inconsistency may be the use of a validated survey for insomnia in the former studies versus screening for sleep disturbances using a subjective sleep quality questionnaire in the latter.…”
Section: Discussionmentioning
confidence: 98%
“…It is a serious public health problem all over the world. Apart from the most widely known microvascular and macrovascular complications associated with diabetes, comorbidities such as fatigue, depression, and sleep disturbances affect the quality of life and the compliance to treatments of patients with diabetes (1,2). Fatigue is a common symptom in the general population that is known to be associated with different etiologies, negatively affecting both physical and mental capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The literature studies concerning patients affected with type 1 (T1D) and 2 (T2D) diabetes mellitus suggest the duration of diabetes mellitus, glycemic control, the frequency and severity of hypoglycemic attacks, depression, sleep problems, microvascular complications, pain, and body mass indices are the major predisposing factors for developing fatigue (2,6,7). Fatigue is also known to impair the compliance of treatment and disturb the glycemic control of patients with diabetes (1,2). Depression is frequent comorbidity associated with diabetes, as recent studies documented that depression affects up to 25% of patients and the risk of major depression is doubled in patients with T2D (8).…”
Section: Introductionmentioning
confidence: 99%